2014
DOI: 10.1075/hcp.43.11sha
|View full text |Cite
|
Sign up to set email alerts
|

A diachronic corpus-based multivariate analysis of “I think that” vs. “I think zero”

Abstract: This corpus-driven study seeks to explain the choice between the zero complement and the that complement constructions, when occurring with the mental state predicate think. Previous studies have identified a range of factors that are argued to explain the alternation patterns. Such studies have also proposed that there is a diachronic drift towards zero complementation. Based on a sample of 9,720 think tokens, from both spoken and written corpora, from between 1560–2012, we test the hypothesis of diachronic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The full details for all nine verbs in terms of that/zero forms per year and their frequency of occurrence per million words per period is found in the Appendix, Tables9-15.13 The coding for tense was divided into four categories: past (which included simple, progressive, perfect and perfect progressive forms), present (again encompassing simple, progressive, perfect and perfect progressive forms), future (auxiliary and non-finite future forms) and n/a (forms consisting of an auxiliary or a non-finite form other than a future form).14 InShank et al (2014) we found that the pronoun form it was a significantly strong predictor itself relative to other pronouns as a complement clause subject for the zero form; therefore, it is now coded independently from all other pronominal forms.15 Note that we do not specifically consider 'I.or.U' (first or second person singular pronouns) as an individual factor because of the redundancy vis-à-vis the factors 'Person' and 'Number' (at the suggestion of Stefan Th. Gries).…”
mentioning
confidence: 99%
“…The full details for all nine verbs in terms of that/zero forms per year and their frequency of occurrence per million words per period is found in the Appendix, Tables9-15.13 The coding for tense was divided into four categories: past (which included simple, progressive, perfect and perfect progressive forms), present (again encompassing simple, progressive, perfect and perfect progressive forms), future (auxiliary and non-finite future forms) and n/a (forms consisting of an auxiliary or a non-finite form other than a future form).14 InShank et al (2014) we found that the pronoun form it was a significantly strong predictor itself relative to other pronouns as a complement clause subject for the zero form; therefore, it is now coded independently from all other pronominal forms.15 Note that we do not specifically consider 'I.or.U' (first or second person singular pronouns) as an individual factor because of the redundancy vis-à-vis the factors 'Person' and 'Number' (at the suggestion of Stefan Th. Gries).…”
mentioning
confidence: 99%
“…when are omissible complementizers actually omitted (e.g. Elsness, 1984;Kaltenböck, 2009;Shank and Cuyckens, 2010)? A number of factors have been argued to be involved, including complexity: simplicity favors omission, so that for instance, omissible complementizers are more often omitted in complements with an easily accessible pronominal subject than in complements with a less easily accessible nominal subject (see e.g.…”
Section: Complementizer Omissionmentioning
confidence: 99%
“…Clausal complementation has been studied from many different perspectives, both diachronically and synchronically, and depending on whether the complement clause is finite or non-finite. Studies on finiteness have primarily concentrated on the variation between clauses introduced by that or by a zero complementizer (Elsness 1984;Fanego 1990aFanego , 1990bFinegan and Biber 1995;Kaltenböck 2006;Shank, Plevoets and Cuyckens 2014; among many others) and by que in Spanish (Delbecque and Lamiroy 1999; Barraza Carbajal 2006; to name just a couple); leaving aside the variation in interrogative complement clauses, as in examples ( 1) to (3), introduced by the conjunctions if and whether in English and only one variant in Spanish, si. In English, the variation between these two conjunctions has been overlooked in prior research, with only a few exceptions such as Stuurman (1990), Eckardt (2007) or Gawlik (2013).…”
Section: If/whether Variation In English and Their Spanish Equivalentsmentioning
confidence: 99%